The Effect of Goji berry Extract on Chemical and Sensory Quality of Meatballs Prepared from Rainbow Trout (Oncorhynchus mykiss Walbaum, 1792) - Çoban, Özlem Emir (Durmuş Ali ARSLAN, 2024)
In this study, the effect of different proportions of goji berry extract (2% and 4%) on the chemical and sensory quality of rainbow trout patties during refrigerated storage (4°C) was evaluated. Goji berry extract stabilized lipids (TBA). Biochemical changes (TVB-N, pH) were maintained. Goji berry-added meatballs stored in Styrofoam packs under refrigerator conditions exceeded acceptable limits on day 15. In addition, according to sensory quality evaluation, the samples supplemented with goji berry extract showed superior sensory quality compared to the control, while the control group was considered unacceptable at day 9. In conclusion, goji berry extract exhibited preservative quality and maintained biochemical and sensory quality.

Bu çalışmada, farklı oranlarda kullanılan goji berry ekstraktının (%2 ve %4) gökkuşağı alabalığı köftelerinin buzdolabında depolama (4°C) sırasında kimyasal ve duyusal kalitesi üzerindeki etkisi değerlendirildi. Goji berry ekstrakt lipitlere (TBA) stabilite kazandırdı. Biyokimyasal değişiklikler (TVB-N, pH) korundu. Strafor paket içinde buzdolabı koşullarında depolanan goji berry ilaveli köftelerin 15. günde kabul edilebilir sınırları aştığı belirlendi. İlaveten, duyusal kalite değerlendirmesine göre, goji berry ekstraktı ilave edilen örnekler kontrole göre üstün duyusal kalite gösterdi, Kontrol grubu 9. günde kabul edilemez olarak değerlendirildi. Sonuç olarak, goji berry ektraktı koruyucu kalite sergileyerek biyokimyasal ve duyusal kaliteyi korudu.
Gökkuşağı Alabalığı (Oncorhynchus mykiss Walbaum,1792)'ndan Hazırlanan Köftelerin Kimyasal ve Duyusal Kalitesi Üzerine Gojiberry Ekstraktın Etkisi
Keywords: Fisheries Technologies; Su Ürünleri Teknolojileri